Effect of antibiofilm compounds on cell viability and biofilm formation single and multi-species on hydroxyapatite and PEEK discs - Morsch, Carolina Schäffer (2019)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Ciências da Saúde, Programa de Pós-Graduação em Odontologia, Florianópolis, 2019.